2002
DOI: 10.1099/0022-1317-51-7-557
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of fim3 and flaA TTGE sequence types amongst isolates of Bordetella bronchiseptica from different host animals

Abstract: Isolates of Bordetella bronchiseptica associated with different animal hosts were analysed by fim3 and flaA genotyping by temporal temperature gradient gel electrophoresis (TTGE). All the isolates from cats (n 138), dogs (n 42) and pigs (n 13) could be assigned to one of two fim3 and one of three flaA TTGE sequence types, respectively. Two avian isolates and a marmoset isolate exhibited novel fim3 sequence types. Dominant but different TTGE sequence types were apparent in isolates from dogs and pigs for both f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…Results obtained in prior studies using a variety of methods suggest a considerable degree of genetic diversity exists among B. bronchiseptica isolates, including those obtained from a single host or from the same geographical region (Khattak & Matthews, 1993;Gueirard et al, 1995; Binns et al, 1998;Keil & Fenwick, 1999;Register & Magyar, 1999;Shina et al, 2002). In contrast, ribotyping, MLST and pertactin repeat region sequence analysis reported here confirm and extend the findings of a prior investigation suggesting a highly clonal population of B. bronchiseptica is found in seals of the North Sea (Register et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Results obtained in prior studies using a variety of methods suggest a considerable degree of genetic diversity exists among B. bronchiseptica isolates, including those obtained from a single host or from the same geographical region (Khattak & Matthews, 1993;Gueirard et al, 1995; Binns et al, 1998;Keil & Fenwick, 1999;Register & Magyar, 1999;Shina et al, 2002). In contrast, ribotyping, MLST and pertactin repeat region sequence analysis reported here confirm and extend the findings of a prior investigation suggesting a highly clonal population of B. bronchiseptica is found in seals of the North Sea (Register et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…By using TGGE method, we need standard specimen of each species of Borrelia to be electrophoresed in the same gel, in order to identify a species of unknown origin by a comparison of the relative position of the DNA bands. The same principle of species differentiation by TGGE was used in several studies: Monstein et al [16] identified enterococcal isolates and profiling bacterial flora from gastric biopsies [16]; Vasquez et al [31] made identification of Lactobacillus species; and Shina et al [19] performed typing of B. bronhiseptica isolates. We believe that the TGGE method, in comparison with PFGE and restriction of PCR product, has advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Among others, TGGE has proven to be a useful tool in genetic analyses of various pathogenic species of bacteria or bacterial strains differentiation [16][17][18][19]. TGGE method enables differentiation of duplex DNA fragments of the same length, but different nucleotide sequence [20].…”
Section: Introductionmentioning
confidence: 99%
“…haemagglutinin (fha), fimbriae (fim2, fim3, fimX and fimA) and pertactin (prn), and exotoxins as bifunctional adenylate cyclase haemolysin (achly), dermonecrotic toxin (dnt) and tracheal colonization factor (tcfA) (Cotter and Miller, 2001;Shina et. al.…”
Section: Introductionmentioning
confidence: 99%